Functionality of primary hepatic non-parenchymal cells in a 3D spheroid model and contribution to acetaminophen hepatotoxicity - Bell, Catherine C.; Chouhan, Bhavik; Andersson, Linda C.; Andersson, Håkan; Dear, James W.; Williams, Dominic P.; Söderberg, Magnus (Archives of toxicology, 2020)
In addition to hepatocytes, the liver comprises a host of specialised non-parenchymal cells which are important to consider in the development of in vitro models which are both physiologically and toxicologically relevant. We have characterized a 3D co-culture system comprising primary human hepatocytes (PHH) and non-parenchymal cells (NPC) and applied it to the investigation of acetaminophen-induced toxicity. Firstly, we titrated ratios of PHH:NPC and confirmed the presence of functional NPCs via both immunohistochemistry and activation with both LPS and TGF-β. Based on these data we selected a ratio of 2:1 PHH:NPC for further studies. We observed that spheroids supplemented with NPCs were protected against acetaminophen (APAP) toxicity as determined by ATP (up to threefold difference in EC 50 at day 14 compared to hepatocytes alone) and glutathione depletion, as well as miR-122 release. APAP metabolism was also altered in the presence of NPCs, with significantly lower levels of APAP-GSH detected. Expression of several CYP450 enzymes involved in the bioactivation of APAP was also lower in NPC-containing spheroids. Spheroids containing NPCs also expressed higher levels of miRNAs which have been implicated in APAP-induced hepatotoxicity, including miR-382 and miR-155 which have potential roles in liver regeneration and inflammation, respectively. These data indicate that the interaction between hepatocytes and NPCs can have significant metabolic and toxicological consequences important for the correct elucidation of hepatic safety mechanisms.